Determination of Cooling Water Requirement for Plastic Film Extrusion Process at PT. XYZ North Sumatra - Paranita, Darni; Donda, Donda; Simatupang, Dimas Frananta (Justek : Jurnal Sains dan Teknologi, 2023)
Abstract:  The cooling water is a liquid medium used to cool down plastic film after it undergoes melting in the plastic film extrusion process. This research aims to determine the required amount of cooling water needed to cool the plastic film before it enters the cutting process. The research method involved collecting primary data from the factory and determining the heat and cooling water requirements using thermodynamic equation calculations. The results indicate that a flow rate of 475 kg/hour of plastic film releases heat into the cooling water at an average rate of 19175.9043 kcal/hour, with an average cooling water requirement of 983.366925 L/hour.Abstrak: Air pendingin merupakan media cairan yang digunakan untuk pendinginan film plastik setelah mengalami peleburan pada proses ekstrusi film plastik. Penelitian ini dilakukan dengan tujuan untuk menentukan jumlah air pendingin yang diperlukan untuk mendinginkan film plastik sebelum nantinya masuk ke dalam proses pemotongan. Metode penelitian dengan pengumpulan data primer dari pabrik dan menenetukan panas serta kebutuhan air pendingin dengan kalkulasi persamaan termodinamika. Hasil menunjukkan bahwa sebanyak 475 kg/jam laju alir kapasitas film plastik melepas panas ke air pendingin dengan rata-rata sebesar 19175,9043 kkal/jam dengan kebutuhan air pendingin rata-rata sebesar 983,366925 L/jam.